Reimagining Neurological Care: A Value-Based Approach - Moore, Janine M.; Phillips, Tim D.; Ahmed, Aiesha (Seminars in Neurology, 2025)
Value-based care has been impactful in primary care, but specialty care has not been a large focus area. This manuscript provides neurologists with an overview of value-based payment (VBP) models and offers practical suggestions for engaging in these models using example conditions of migraine and dementia. The article discusses various VBP models, from low-risk pay-for-performance to high-risk shared risk models, and emphasizes the importance of data infrastructure, patient outcomes, quality improvement, and cost reduction for success in value. By adopting a value-based approach, neurologists can improve care for complex neurological conditions, enhance patient satisfaction, and achieve sustainable health care excellence. The conclusions highlight the transformative potential of VBP models in neurology, encouraging neurologists to take small steps toward value-based care to achieve quadruple aim benefits.
Keywords: value; value based care; value based payment